Seeking health information in rural context: Exploring sources of maternal health information in rural Tanzania - Kassim, Mohamed; Katunzi-Mollel, Kokuberwa Rehema Upendo (University of Dar es Salaam Library Journal, 2018)
Sources of information differ with regard to the extent to which it is obtained to meet the information needs of the information users. This study examined the sources of information used by women in rural Tanzania to meet their different maternal health information needs. In all, 380 women of the reproductive age were involved in the study. The study utilised a mixed methods research approach that integrates both the qualitative and quantitative dimensions of research. Information from respondents was collected using questionnaires and focus group discussions. The study found that women used different sources of information to satisfy their maternal health information needs. Despite the majority of the women (93%) preferring to use professional healthcare workers as their sources of information, they received most of it from the informal sources such as community healthcare workers (CHWs), traditional birth attendants (TBAs), and their immediate family members. The use of the informal sources by the majority of the women was attributed to limited access to professional healthcare in most of the villages under review. The study recommends that while improvement of access to professional health care in rural areas is imperative, empowerment of CHWs and TBAs is also necessary for them to be able to provide timely and relevant maternal health information to the expectant mothers in all areas where health facilities are not available.